2019
DOI: 10.3889/oamjms.2019.245
|View full text |Cite
|
Sign up to set email alerts
|

The The Effects of Cinnamaldehyde (Cinnamon Derivatives) and Nystatin on Candida Albicans and Candida Glabrata

Abstract: BACKGROUND: Candida species are the most common opportunistic fungal infections. Today, cinnamon plants have been considered for anti-Candida properties. AIM: This study aimed to investigate the effectiveness of cinnamaldehyde extract (from cinnamon derivatives) on Candida albicans and Candida glabrata species and comparison with nystatin. MATERIAL AND METHODS: In this study, cinnamaldehyde and nystatin were used. The specimens included Candida albicans and Candida glabrata. Minimum inhibitory conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
8
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 20 publications
3
8
0
2
Order By: Relevance
“…Research, Society and Development, v. 10, n. 10, e554101019027, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org /10.33448/rsd-v10i10.19027 Our results are consistent with newly published findings that showed that these molecules were effective at antimicrobial activity against C. albicans and C. Glabrata (Trinh et al, 2011;Dogan et al, 2017;Bakhtiari 2019). However, here we highlight the effectiveness cinnamaldehyde and α-terpineol on inhibiting growth of C. krusei.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Research, Society and Development, v. 10, n. 10, e554101019027, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org /10.33448/rsd-v10i10.19027 Our results are consistent with newly published findings that showed that these molecules were effective at antimicrobial activity against C. albicans and C. Glabrata (Trinh et al, 2011;Dogan et al, 2017;Bakhtiari 2019). However, here we highlight the effectiveness cinnamaldehyde and α-terpineol on inhibiting growth of C. krusei.…”
Section: Discussionsupporting
confidence: 90%
“…As investigations now point to the antimicrobial effect of cinnamaldehyde and α-terpineol in several reference strains (Dogan et al, 2017., Pootong et al, 2017Bakhtiari et al, 2019), we also investigated antifungal effects in clinical isolated of C. albicans. Although reference strains are widely used in microbiology reports, the evaluation against clinical isolates strains demonstrate a challenge to antifungal drugs due to phenotypic modifications in the cells, which could interfere in the action these drugs (Akers et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The attention of many researchers has focused on the antimicrobial properties of traditional medical substances, like essential oils (EOs) [ 5 , 6 , 7 ]. EOs and extracts have demonstrated effective antibacterial and antifungal properties [ 8 , 9 , 10 , 11 ]. In the field of dental medicine, oral hygiene products based on herbal extracts are well-known [ 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cinnamaldehyde has shown a wide spectrum of antimicrobial activity by inhibiting pathogens such as Candida spp. [ 13 , 14 ], E. coli [ 15 ], Listeria monocytogenes [ 16 ], Pseudomonas aeruginosa [ 17 ], and Staphylococcus aureus [ 18 ]. Most of the studies carried out with this compound are related to the food industry, where it is especially used for its antimicrobial properties [ 12 ].…”
Section: Introductionmentioning
confidence: 99%